Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Umkm dengan Tax Amnesty sebagai Pemoderasi - Yunita Eriyanti Pakpahan; Eni Duwita Sigalingging (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
The role of SMEs as an economic driver of 60% for the country of Indonesia today. Therefore the government has provided tax breaks to help SMEs continue to grow. But there are still many SMEs that have not complied to fulfill their obligations. The tax relief in the form of a reduction in tax rates and the tax amnesty program is expected to be able to encourage taxpayer compliance aim of the research was to find out, analyze, and prove empirically service quality, understanding of taxation regulation, taxation socialization, and sanction on small and medium-sized enterprises (SMEs) taxpayer compliance and tax amnesty as moderating in KPP Medan Polonia using Structural Equation Modeling (SEM) with Partial Least Square (PLS) analysis. The population of this research is small and medium-sized enterprises taxpayer and participated in the tax amnesty program at KPP Polonia Medan (tax office) totaling 5.718. The sampling technique chosen was accidental sampling with solving formula obtained 98 samples. Results of path coefficient analysis showed that service quality, understanding of taxation regulation and taxation socialization influences SMEs taxpayers’ compliance and sanction doesn’t influence  on SMEs taxpayers’ compliance. Tax amnesty as a moderating variable has an influence on  understanding of taxation regulation and taxation socialization with taxpayer compliance but can’t moderate the effect of service quality and sanction with SMEs taxpayers’ compliance